2007
DOI: 10.1111/j.1751-1097.2007.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Psoralen DNA Crosslinking Kinetics Associated with a Triplex‐forming Oligonucleotide

Abstract: A triplex-forming oligonucleotide (TFO), HPRT3, conjugated to a psoralen derivative, was designed to target a psoralen reaction site within the HPRT gene. HPRT3 bound with high affinity to a synthetic duplex target sequence. At a uniform UVA radiation dose, the ratio of psoralen monoadducts (MA) to interstrand crosslinks decreased and inverted with increasing TFO concentration. As the TFO concentration increased from 10 nm to 10 microm, the efficiency of psoralen MA formation remained relatively constant but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The rate of photochemically induced monoadduct formation (k 1 ) increases with improved triplex stability (Takasugi et al, 1991;Giovannangeli et al, 1992;Perkins et al, 1999) and is therefore strongly dependent on TFO concentration, whereas k 2 is independent on TFO concentration and may be influenced by the external macromolecular environment (Oh et al, 2008).…”
Section: Crosslinkmentioning
confidence: 99%
“…The rate of photochemically induced monoadduct formation (k 1 ) increases with improved triplex stability (Takasugi et al, 1991;Giovannangeli et al, 1992;Perkins et al, 1999) and is therefore strongly dependent on TFO concentration, whereas k 2 is independent on TFO concentration and may be influenced by the external macromolecular environment (Oh et al, 2008).…”
Section: Crosslinkmentioning
confidence: 99%
“…Further UVA radiation allows certain monoadducts to react further to form DNA interstrand crosslinks (XL). These photochemical reactions also occur when psoralens are targeted by a TFO, and have been characterized in detail [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that such site-specific selectivity is achievable. Notable are extensive studies with psoralen-conjugates, that upon UV irradiation lead to stable cross-links on the target duplex DNA . Some ODN-conjugates have shown site-specific photoreactivity upon irradiation in the visible region , and only very few reports have applied dyes that have relevant wavelengths for in vivo applications (i.e.…”
Section: Introductionmentioning
confidence: 99%